PERMINTAAN PARIWISATA INDONESIA: STUDI KASUS WISATAWAN MALAYSIA - Devanto Shasta Pratomo (Journal of Indonesian Applied Economics, 2009)
This research attempts to study the effect of income per capita in Malaysia (GDP),relative  prices  (CPI)  and Visit  Indonesia Year  1991  to  Indonesia  tourism demandamong Malaysian visitors. Malaysian visitors’ arrivals  to  Indonesia are used as aproxy of  Indonesia  tourism demand among Malaysian visitors.  In other words, anincrease in the Malaysian visitor arrivals to Indonesia indicates an increase in thetourism demand among Malaysian visitors, vice versa. The data used in  this studyare quarterly secondary data for the period 1989.1-1997.4 consisting of total Malay-sian visitor arrival to  Indonesia, income per capita in Malaysia, and ratio of con-sumer price  index of Indonesia  to consumer price  index of Malaysia. The analysismethod applied in this study is regression using Error Correction Model (ECM). Theresults show that income per capita of Malaysia is elastic and positively affects Ma-laysian visitor arrivals  to  Indonesia. On the other hand, relative prices negativelyaffect Malaysian visitor arrivals to Indonesia, while Visit Indonesia Year 1991 posi-tively affects Malaysian visitor arrivals to Indonesia.Keywords: tourism, GDP, CPI, and ECM